2010
DOI: 10.1038/ismej.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

GeoChip 3.0 as a high-throughput tool for analyzing microbial community composition, structure and functional activity

Abstract: A new generation of functional gene arrays (FGAs; GeoChip 3.0) has been developed, with ∼28 000 probes covering approximately 57 000 gene variants from 292 functional gene families involved in carbon, nitrogen, phosphorus and sulfur cycles, energy metabolism, antibiotic resistance, metal resistance and organic contaminant degradation. GeoChip 3.0 also has several other distinct features, such as a common oligo reference standard (CORS) for data normalization and comparison, a software package for data manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
209
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 280 publications
(212 citation statements)
references
References 60 publications
3
209
0
Order By: Relevance
“…Spots with a signal-to-noise ratio of Ͻ2 and outliers of replicates were removed. The signal intensities were normalized within and across samples based on the mean signal intensity, as described previously (28). We then averaged the normalized signal intensities for the three replicates for each WWTP to conduct downstream analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Spots with a signal-to-noise ratio of Ͻ2 and outliers of replicates were removed. The signal intensities were normalized within and across samples based on the mean signal intensity, as described previously (28). We then averaged the normalized signal intensities for the three replicates for each WWTP to conduct downstream analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The community DNA was extracted using a freeze-grinding method (24) and quantified with PicoGreen (25) (Quant-It PicoGreen kit; Invitrogen, Carlsbad, CA). DNA (20 ng) was amplified using whole-community genome amplification with a TempliPhi kit (GE Healthcare, Piscataway, NJ), and 3.0 g amplified DNA was hybridized to the GeoChip 3.0 as previously described (26,27). The hybridized GeoChip was scanned, and the signal intensity for each spot was determined using ImaGene 6.0 (Biodiscovery, El Segundo, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Both the 16S rRNA-based prediction and the GeoChip 5.0 analysis, which has been used to assess the metabolic pathways in other ecosystems (40,42,(61)(62)(63), showed that these communities possess a diverse and versatile metabolic potential. However, communities were separated based on plant microenvironment only via GeoChip analysis, indicating that predictions can yield valuable global information but may not be an adequate reflection of the community variations detected only when analyzing samples directly.…”
Section: Figmentioning
confidence: 99%